Empowering Green Innovation: How CEO and Firm-Level Factors Shape Sustainable Business Growth in Indonesia - Nuraini Sari; Tri Ayu Astari; Pariang Siagian; Nafis Dwi Kartiko (Bina Nusantara University, 2025)
Climate change, driven by global warming, is a critical global issue affecting air quality and the environment. In response, many companies are adopting sustainable practices such as green product innovation. The research examined the impact of CEO and firm-level factors on financial performance through green product innovation in the raw material-producing sector listed on the Indonesia Stock Exchange from 2020 to 2022. The research focused on five key variables: CEO education, gender, experience, firm size, and firm age, analyzing their effects on the adoption of green product innovation and subsequent impact on company growth and profitability. Secondary data were collected from the company's annual and sustainability reports using purposive sampling, resulting in a sample of 81 companies over three years. Data were analyzed using multiple linear regression and mediation tests. The results show that CEO gender and experience have a significant positive effect on green product innovation, while CEO education does not show a significant effect. Additionally, larger and older companies are more likely to implement green innovations due to their established resources and capacities. Green product innovation positively influences financial performance, reflected in increased sales and operational efficiency. These results suggest that both CEO and firm-level factors play a key role in driving sustainability initiatives that contribute to long-term business growth. The research provides valuable insights for companies aiming to enhance their sustainability strategies and for policymakers encouraging green innovation. Managerial implications point to the importance of fostering experienced leadership and leveraging company resources to support environmentally responsible innovation.